2020
DOI: 10.1136/bmjopen-2020-039394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particulate matter exposure on patients with COPD and risk reduction through behavioural interventions: the protocol of a prospective panel study

Abstract: IntroductionPatients with chronic obstructive pulmonary disease (COPD) are vulnerable to particulate matter (PM) exposure which can increase acute exacerbations and hospitalisation. Interventions to avoid PM exposure are important but evidence-based guidance is lacking. This study aims to assess the impact of PM on lung function, quality of life and exacerbations in patients with COPD using a panel design study; it will also provide evidence for interventional measures to reduce harm from PM exposure.Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The above results demonstrated that CS could promote the cellular uptake of PS-NPs and evoke higher ROS level in a strain-dependent manner, which caused cellular oxidative stress and even cell apoptosis. These results were consistent with the view that atmospheric particulate matter exposure contributed significantly to the development and exacerbation of acute respiratory distress syndrome (pathological strain). , …”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The above results demonstrated that CS could promote the cellular uptake of PS-NPs and evoke higher ROS level in a strain-dependent manner, which caused cellular oxidative stress and even cell apoptosis. These results were consistent with the view that atmospheric particulate matter exposure contributed significantly to the development and exacerbation of acute respiratory distress syndrome (pathological strain). , …”
Section: Results and Discussionsupporting
confidence: 91%
“…These results were consistent with the view that atmospheric particulate matter exposure contributed significantly to the development and exacerbation of acute respiratory distress syndrome (pathological strain). 56,57 Real-Time Monitoring of PS-NPs-Induced H 2 O 2 Release from Alveolar Cells during Cyclic Stretching.…”
Section: Fabrication and Characterization Of Stretchablementioning
confidence: 99%
“…We conducted a prospective cohort study at four referral hospitals in South Korea between 2019 and 2020, to assess the association between ambient PM 2.5 concentrations and clinical parameters in patients with COPD over 1-year period. The detailed protocols [ 30 , 31 ] and preliminary results [ 32 ] have been previously published. The study was individually approved by the Institutional Review Boards.…”
Section: Methodsmentioning
confidence: 99%
“…This study was approved by the Institutional Review Boards of Asan Medical Center (2019-0476), Ulsan University Hospital (2019–07–049), Gangneung Asan Hospital (2019-06-049), and Gil Medical Center (GBirb2019-290). The detailed study design was published previously 13 .…”
Section: Methodsmentioning
confidence: 99%
“…All questionnaires were completed twice, at enrollment and the end of the study (1 year). Information about educational level and economic status was also collected 13 . Patients attending Asan Medical Center underwent serial impulse oscillometry.…”
Section: Methodsmentioning
confidence: 99%